2010
DOI: 10.1007/s00105-010-1961-4
|View full text |Cite
|
Sign up to set email alerts
|

Verruköses spinozelluläres Karzinom auf Lichen ruber hypertrophicus

Abstract: Lichen planus is a chronic mucocutaneous T-cell-mediated disease, whose cause is still unknown. The first case of lichen planus that transformed into squamous cell carcinoma was reported in 1903. We present three patients in whom squamous cell carcinomas were identified in chronic lichen planus. The world literature includes at least 91 cases, including our three cases. In an epidemiological study, no significant risk of transformation of cutaneous lichen planus into squamous cell carcinomas was found. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the meta-analysis of Sigurgeirsson and Lindelöf (1991) 36 reports of SCC associated with lichen planus were analysed among 2071 lichen planus patients [10]. In 2011, Friedl et al reported on three patients who developed an SCC on chronic lichen planus of the lower leg and analysed another 24 cases within five years [11]. Five more cases have been reported since then in the international literature, mostly on lower legs and in association with hypertrophic or verrucous lichen planus [12], [13], [14], [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis of Sigurgeirsson and Lindelöf (1991) 36 reports of SCC associated with lichen planus were analysed among 2071 lichen planus patients [10]. In 2011, Friedl et al reported on three patients who developed an SCC on chronic lichen planus of the lower leg and analysed another 24 cases within five years [11]. Five more cases have been reported since then in the international literature, mostly on lower legs and in association with hypertrophic or verrucous lichen planus [12], [13], [14], [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…4 There are reports of metastatic squamous cell carcinoma and keratoacanthoma arising from long standing hypertrophic lesions of lichen planus. 6,7 The morphology can be very varied ranging from hyperkeratotic papules to extremely thick plaque type of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1903 over 90 cases of malignant transformation of cutaneous LP into squamous cell carcinoma have been described, with a higher incidence in hypertrophic LP and the possibility to metastasize [94,95]. In oral LP a higher risk has been proven and the WHO defines oral LP as a ‘premalignant condition' [96,97].…”
Section: Discussionmentioning
confidence: 99%